The Role of Temporal Modulation in Sensorimotor Interaction - Goldstein, Louis (Frontiers in Psychology, 2019)
How do we align the distinct neural patterns associated with the articulation and the acoustics of the same utterance in order to guide behaviors that demand sensorimotor interaction, such as vocal learning and the use of feedback during speech production? One hypothesis is that while the representations are distinct, their patterns of change over time (temporal modulation) are systematically related. This hypothesis is pursued in the exploratory study described here, using paired articulatory and acoustic data from the X-ray microbeam corpus. The results show that modulation in both articulatory movement and in the changing acoustics has the form of a pulse-like structure related to syllable structure. The pulses are aligned with each other in time, and the modulation functions are robustly correlated. These results encourage further investigation and testing of the hypothesis.